A Cross-Sectional Study on Subjective Fever Assessment in Children by Palpation: Are Fathers as Reliable as Mothers?. (12th February 2020) - Rosenbloom, Ehud; Balis, Crysta; Jacobson, Dustin; Conway, Melanie; Cheng, Ji; Kozer, Eran
Abstract : Background . Fever is common in pediatric patients. Often, parents rely solely on palpation when assessing their child's fever. The objective of the current study was to determine the accuracy of parents in detecting their child's fever by palpation. Methods . A prospective cross-sectional study was conducted at the emergency department (ED) of a tertiary pediatric hospital. Infants and children, 0–4 years of age, presenting to the ED with both parents were included. Parents were separately asked if their child had a fever and, if so, were asked to assess the temperature by palpation. A nurse obtained the rectal temperature. The primary outcome measure was the accuracy of fathers and mothers in detecting fever. Results . A total of 170 children with their parents were enrolled. The mean ages of the children, mothers, and fathers were 18.9 (SD 0.8) months, 31.1 (SD 6.4) years, and 33.7 (SD 6.9) years, respectively. No statistically significant difference was found between mothers and fathers in the ability to assess fever by palpation (OR 0.65, 95% CI 0.39, −1.08). Sensitivities for detecting fever by palpation for mothers and father were 86.4% and 88.2%, respectively (specificity among mothers: 54.2% and specificity among fathers: 43.1%). The overall negative and positive predictive values were 65.9% (95% CI 55%–75.7%) and 75.7% (95% CI 69.9%–80.8%), respectively. Conclusions . Mothers and fathers do not differ in their ability to accurately assess their child's fever by palpation. The low positive and negative predictive values indicate that if temperature was not measured, physicians cannot rely on parents' reports.